IMPLEMENTASI EDUKASI GIZI DAN PENGUKURAN ANTROPOMETRI SEBAGAI KUNCI PENCEGAHAN MALNUTRISI PADA BALITA - Kholilah Lubis; Zilfi Yola Pitri; Indah Putri Ramdhanti; Desri Nova H (Jurnal Pengabdian Masyarakat, 2026)
Background: Malnutrition among toddlers remains a significant public health problem that affects the quality of human resources in the future. Nutrition education is one of the important promotive and preventive interventions in improving parents’ knowledge regarding the fulfillment of children's nutritional needs. Objective: This community service activity aims to improve parents’ knowledge regarding the prevention of malnutrition among toddlers in the working area of Gulai Bancah Public Health Center, Bukittinggi City. Methods: The method used was an educational approach aimed at assessing changes in participants’ knowledge levels before and after the nutrition education intervention among 18 respondents. The intervention was conducted through counseling using presentation media, leaflets, and demonstrations of toddler growth measurement. Results: The results showed an increase in the mean knowledge score from 53.44 to 73.28, with a p-value of 0.001 (p < 0.05), indicating a significant difference after the intervention. Thus, nutrition education has been proven effective in improving parents’ knowledge as an effort to prevent malnutrition among toddlers and should be implemented continuously. Keywords: Nutrition education, Malnutrition, Toddlers, Knowledge, Prevention